(untitled) (Research, Society and Development, 2021)
Fluorosis occurs when fluoride is chronically ingested in small amounts, during the amelogenesis phase of permanent teeth, when there is less protein reabsorption, leading to the formation of a more porous tooth enamel, characterized by whitish streaks. These changes are seen symmetrically in homologous teeth, because intraosseous development takes place at the same time. These striations may present whitish to brownish in the affected teeth. The aim of this paper is to present an alternative to the clinical case of a 10-year-old patient who presented with dental fluorosis. The clinical planning for this case was to use the microabrasion technique on tooth enamel based on 6% hydrochloric acid and silicon carbide. Just one appointment was enough to improve the patient’s esthetics and high esteem. We conclude that the technique and the material used provided a harmony of white stains and positively impacted the patient’s quality of life and high esteem. Another point to be considered is that this technique is accessible and requires minimal intervention, since it preserved the tooth structure, not causing any damage or sensitivity to the teeth.